A Multidimensional Virtual Reality Neurorehabilitation Approach to Improve Functional Memory: Who Is the Ideal Candidate? - Di Tella, Sonia; Isernia, Sara; Pagliari, Chiara; Jonsdottir, Johanna; Castiglioni, Carlotta; Gindri, Patrizia; Gramigna, Cristina; Canobbio, Samuela; Salza, Marco; Molteni, Franco; Baglio, Francesca (Frontiers in Neurology, 2021)
Aims: We aimed to identify the significant predictors of ecological memory amelioration after the Human Empowerment Aging and Disability (HEAD) rehabilitation program, a multidimensional treatment for chronic neurological diseases. Materials and Methods: 93 patients with Parkinson’s Disease (N=29), Multiple Sclerosis (N=26), and stroke (N=38) underwent a multidimensional rehabilitation. We focused on changes after treatment on ecological memory (outcome measure) evaluated by Rivermead Behavioural Memory Test-Third Edition (RBMT-3). Minimal Clinical Changes (MCID) after treatment were calculated for RBMT-3. The change score on RBMT-3 was categorized in positive effect, stabilization, or no effect of the treatment. Random forest classification identified who significantly benefited from treatment against who did not in terms of ecological memory functioning. Accordingly, logistic regression models were created to identify the best predictors of the treatment effect. A predicted probability value was derived and the profile of the ideal candidate of HEAD protocol was shown by combining different ranks of significant predictors in a 3x3 matrix for each pair of predictors. Results: A significant number of cases reported positive effect of the treatment on ecological memory, with an amelioration over the MCID or a stabilization. The random forest analysis highlighted a discrete accuracy of prediction (> 0.60) for all the variables considered at baseline for identifying participants who significantly benefited and who did not from the treatment. Significant logistic regression model (Wald method) showed a predictive role of Montreal Cognitive Assessment (MoCA; p = 0.007), 2 Minute Walk Test (2MWT; p = 0.038) and RBMT-3 (p < 0.001) at baseline on HEAD treatment effect. Finally, we observed a high probability of success in people with higher residual cognitive functioning (MoCA; Odds ratio = 1.306) or functional mobility (2MWT; Odds ratio = 1.013). Discussion: The HEAD program is a rehabilitation with effects on multiple domains, including ecological memory. Residual level of cognitive and/or motor functioning is a significant predictor of the treatment success. These findings confirm the intrinsic relationship subsisting between motor and cognitive functions and suggest the beneficial effects of physical activity on cognitive functions and vice versa.